Establishing a methodology for unpaved and paved roads management system - Ribeiro, Laura Carine Pereira (2020)
In the state of Minas Gerais, Brazil, roads are mostly managed by local agencies that carry out more maintenance and rehabilitation (M&R) work than management work. In addition, these agencies have very limited resources and operate without any long- term plans. Overall, there is no available guidelines or consistent strategies followed over the state to manage these kinds of roads. As a result, this work was created to develop a new Unpaved Roads Management System (URMS) and a Pavement Management System (PMS). These URMS and PMS are intended to provide feasible practices to help local agencies in dealing with the various challenges associated with maintaining unpaved and paved roads. The ultimate goal of these URMS and PMS is to help local agencies in maintaining their asset of all the roads in best serviceable shape within available resources. The methodology of this study was to establish a prototype for the new URMS and PMS to improve current management practices for unpaved and paved roads in Minas Gerais. Before implementation across the state, was selected a specific road to carry out the pilot study on the topic, a region at Zona da Mata County, close to Viçosa city. A comprehensive dataset was developed after data collection. This dataset was used to develop various methodologies related to URMS and PMS in Minas Gerais. Statistical techniques were used to establish the new methodologies. These techniques include Markov chains to develop deterioration models and analysis of evolutionary algorithms to develop the decision-making process. As a result, a management program for unpaved and paved roads was developed using practical data entry and statistically reliable results. With this program, small or large cities and companies can better manage their road network, applying specific maintenance, with the best cost-benefit for the competent agency, always aiming at their budget limit. Keywords: Optimization systems. Unpaved roads. Paved roads.